Protocol for a multicentred randomised controlled trial investigating the use of personalised golimumab dosing tailored to inflammatory load in ulcerative colitis: the GOAL-ARC study (GLM dose Optimisation to Adequate Levels to Achieve Response in Colitis) led by the INITIAtive group (NCT 0268772). Issue 1 (11th January 2018) - Sheridan, Juliette; Coe, Carol Ann; Doran, Peter; Egan, Laurence; Cullen, Garret; Kevans, David; Leyden, Jan; Galligan, Marie; O'Toole, Aoibhlinn; McCarthy, Jane; Doherty, Glen
Abstract : Introduction: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD), often leading to an impaired quality of life in affected patients. Current treatment modalities include antitumour necrosis factor (anti-TNF) monoclonal antibodies (mABs) including infliximab, adalimumab and golimumab (GLM). Several recent retrospective and prospective studies have demonstrated that fixed dosing schedules of anti-TNF agents often fails to consistently achieve adequate circulating therapeutic drug levels (DL) with consequent risk of immunogenicity treatment failure and potential risk of hospitalisation and colectomy in patients with UC. The design of GLM dose Optimisation to Adequate Levels to Achieve Response in Colitis aims to address the impact of dose escalation of GLM immediately following induction and during the subsequent maintenance phase in response to suboptimal DL or persisting inflammatory burden as represented by raised faecal calprotectin (FCP). Aim: The primary aim of the study is to ascertain if monitoring of FCP and DL of GLM to guide dose optimisation (during maintenance) improves rates of patient continuous clinical response and reduces disease activity in UC. Methods and analysis: A randomised, multicentred two-arm trial studying the effect of dose optimisation of GLM based on FCP and DL versus treatment as per SMPC. Eligible patients will be randomised in a 1:1 ratio to 1 of 2 treatment groups and shall be treated over a period of 46 weeks. Ethics and dissemination: The study protocol was approved by the Research Ethics committee of St. Vincent's University Hospital. The results will be published in a peer-reviewed journal and shared with the worldwide medical community. Trial registration numbers: EudraCT number: 2015-004724-62; Clinicaltrials.gov Identifier: NCT0268772; Pre-results.